Adsorption of pharmaceuticals pollutants, Ibuprofen, Acetaminophen, and Streptomycin from the aqueous phase using amine functionalized superparamagnetic silica nanocomposite. (20th April 2021) - Chandrashekar Kollarahithlu, Smitha; Balakrishnan, Raj Mohan
Abstract: Pharmaceuticals are one of the emerging pollutants that pose a severe threat to the aquatic habitats, which in turn affects other species in the biosphere. The superparamagnetic based silica nanocomposites modified with aminosilane were characterized for their physicochemical properties and also the purity of the nanocomposite obtained was determined. The adsorptive properties of the nanocomposites were investigated for the removal of pharmaceutical pollutants such as Ibuprofen, Acetaminophen, and Streptomycin from aqueous solutions. The adsorption process of pharmaceuticals was found to reach equilibrium within the first 15 min reporting high removal efficiency of up to 97% for Ibuprofen (IBF) followed by (94%) acetaminophen (ACE) and (70%) streptomycin (STR) for a concentration of 12 mg L −1 . The adsorption process was found to follow the pseudo-second-order kinetics and fits well with the Langmuir isotherm model, confirming the adsorption on to the homogenous surface of the nanocomposite. The amine functional groups formed on the nickel ferrite nanocomposites by coating aminopropyltrimethoxysilane (APTS) were observed to aid the adsorption process. The adsorption capacity of the nanocomposites varies for IBF, ACE, and STR as 59, 58, and 49 mg g −1 at pH 7.0, 6.0, and 5.0, respectively. The amine coated magnetic nanocomposite also showed excellent regeneration capacity for up to four cycles and can be a promising adsorbent, especially for removing of pharmaceutical pollutants from aqueous streams. Graphical abstract: Image 1 Highlights: NFO@SiO2 @APTS show enhanced removal of target pharmaceuticals in the aqueous system. The nanocomposite achieved higher adsorption within the 15th minute. The adsorption process follows the Langmuir adsorption isotherm. Chemisorption aids the adsorption process at pH 5.0, 6.0, and 7.0 for STR, ACE, and IBF. The nanocomposites exhibited excellent recyclability for further reuse.